Elevation of Glucose 6-Phosphate Dehydrogenase Activity Induced by Amplified Insulin Response in Low Glutathione Levels in Rat Liver - Misako Taniguchi; Nobuko Mori; Chizuru Iramina; Akira Yasutake (The Scientific World Journal)
Weanling male Wistar rats were fed on a 10% soybean protein isolate (SPI) diet for 3 weeks with or without supplementing 0.3% sulfur-containing amino acids (SAA; methionine or cystine) to examine relationship between glutathione (GSH) levels and activities of NADPH-producing enzymes, glucose 6-phosphate dehydrogenase (G6PD) and malic enzyme (ME), in the liver. Of rats on the 10% SPI diet, GSH levels were lower and the enzyme activities were higher than of those fed on an SAA-supplemented diet. Despite the lower GSH level, γ-glutamylcysteine synthetase (γ-GCS) activity was higher in the 10% SPI group than other groups. Examination of mRNAs of G6PD and ME suggested that the GSH-suppressing effect on enzyme induction occurred prior to and/or at transcriptional levels. Gel electrophoresis of G6PD indicated that low GSH status caused a decrease in reduced form and an increase in oxidized form of the enzyme, suggesting an accelerated turnover rate of the enzyme. In primary cultured hepatocytes, insulin response to induce G6PD activity was augmented in low GSH levels manipulated in the presence of buthionine sulfoximine. These findings indicated that elevation of the G6PD activity in low GSH levels was caused by amplified insulin response for expression of the enzyme and accelerated turnover rate of the enzyme molecule.